Metastatic cancer-related thrombotic microangiopathies: a cohort study. (August 2014) - Ducos, Guillaume; Mariotte, Eric; Galicier, Lionel; Canet, Emmanuel; Boutboul, David; Lemiale, Virginie; Schlemmer, Benoit; Veyradier, Agnes; Azoulay, Elie; Zafrani, Lara
ABSTRACT : Thrombotic microangiopathies (TMAs) in patients with metastatic cancer are poorly characterized. We recorded 17 patients who had TMAs associated with disseminated solid cancer in our intensive care unit over an 11-year period. We compared them with a group of 20 patients with proven idiopathic thrombotic thrombocytopenic purpura hospitalized during the same period. We aimed to specify the clinical and biological features of cancer-related TMAs (CR-TMAs). CR-TMAs can either be inaugural of the underlying cancer or reflect worsening course. Clues to the presence of CR-TMA include respiratory symptoms, bone pain, myelemia or higher platelet count than in thrombotic thrombocytopenic purpura. In this context, bone marrow aspiration is a fast and gainful investigation to avoid plasmatherapy and immunosuppressive drugs. Indeed, this severe and poor-prognosis disease requires prompt diagnosis and rapid initiation of specific chemotherapy.